Analisis Pengaruh Pasir Pantai Wahede Kabupaten Barru Terhadap Kuat Tekan Dan Tarik Belah Beton - Hasan, Nurhatimah; Mustakim, Mustakim; Fadly, Imam (Sultra Civil Engineering Journal (SCiEJ), 2024)
Barru Regency is a coastal area with abundant potential for Wahede beach sand, which can be used to make economical concrete. This research aims to determine the compressive and tensile strength values of concrete as well as the optimal percentage of the beach sand mixture. The research was carried out at the Structure and Materials Laboratory of the Muhammadiyah University of Parepare, with a planned compressive strength of 20 MPa.The results of research on normal concrete compressive strength at 7 days were 12.27 MPa, 14 days 13.97 MPa, and 28 days 20.29 MPa. Variation: 25%; compressive strength: 7 days 13.58 MPa, 14 days 15.85 MPa, and 28 days 21.89 MPa. Variation 50%, compressive strength 7 days 14.34 MPa, 14 days 18.68 MPa, and 28 days 22.08 MPa. 100% variation, compressive strength: 7 days 14.72 MPa, 14 days 19.34 MPa, and 28 days 25.48 MPa. The split tensile strength of concrete decreases with an increasing percentage of beach sand: normal 28-day concrete 7,852 MPa, 25% variation 6,222 MPa, 50% variation 6,963 MPa, and 100% variation 8,000 MPa